2018
DOI: 10.1002/jcp.27778
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CRMP‐2 phosphorylation by CDK5 restricts the repair of damaged optic nerve

Abstract: Objective To study the mechanism of collapsin response mediator protein‐2 (CRMP‐2) phosphorylation changes and cyclin‐dependent kinase 5 (CDK5) expression after optic nerve injury. Methods Optic nerve injury rat models were constructed, the messenger RNA (mRNA) level of CRMP‐2 in optic nerve tissues was determined by quantitative reverse transcription polymerase chain reaction (qRT‐PCR) after building models 0, 3, 7, and 14 days. The protein expression of CRMP‐2, phospho‐CRMP‐2 (p‐CRMP‐2), and CDK5 were also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Reintroduction of a single fluorine (12, CDK5 IC 50 1.1 nM, 44× selective over CDK2) maintained good potency and hinted that this substituent may be necessary for selectivity. We then Further exploration around the 5-position showed that small alkyl groups such as ethyl (20) and trifluoromethyl (21) maintained the potency and selectivity, as did the more polar isopropoxy substituent (22). While we suspected that the selectivity of 4-substituted compounds such as 15 and 16 may arise from optimization of the hydroxymethyl pyrazole present in 1, the R 5 substituent in 18 and 19 could orient toward either the interior of the binding pocket or toward the solvent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reintroduction of a single fluorine (12, CDK5 IC 50 1.1 nM, 44× selective over CDK2) maintained good potency and hinted that this substituent may be necessary for selectivity. We then Further exploration around the 5-position showed that small alkyl groups such as ethyl (20) and trifluoromethyl (21) maintained the potency and selectivity, as did the more polar isopropoxy substituent (22). While we suspected that the selectivity of 4-substituted compounds such as 15 and 16 may arise from optimization of the hydroxymethyl pyrazole present in 1, the R 5 substituent in 18 and 19 could orient toward either the interior of the binding pocket or toward the solvent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11, 12,13,15,16,17,18,19,20,21,24,29,31, and 32 were prepared in a manner similar to GFB-12630 using the appropriate aniline as a starting material.…”
Section: Lcms Purity 98% Ms (Esi+) 463 (M + H)mentioning
confidence: 99%
See 2 more Smart Citations
“…Cdk5 is found to induce mitochondrial kinetic defects in optic neuropathy (Rong et al, 2020 ). Cdk5 phosphorylates CRMP-2, which will aggravate optic nerve damage (Chen et al, 2019 ). Cdk5 contributes to oxidative stress (Guo et al, 2018 ) and endoplasmic reticulum stress (Shi et al, 2018 ).…”
Section: Other Neurological Disordersmentioning
confidence: 99%